A trial of Itraconazole or Amphotericin B HIV-associated talaromycosis - Le, T; Kinh, N; Cuc, N; Tung, N; Lam, N; Thuy, P; Cuong, D; Phuc, P; Vinh, V; Hanh, D; Tam, V; Thanh, N; et al. (Massachusetts Medical Society, 2017)
Background Talaromyces marneffei infection is a major cause of HIV-related death in South and Southeast Asia. Guidelines recommend initial treatment with amphotericin B deoxycholate but it has significant side effects, high cost and limited availability. Itraconazole is orally available, better- tolerated and widely-used in place of amphotericin; however, these two strategies have not been compared in clinical trials. Methods In this open-label non-inferiority trial, we randomly assigned 440 HIV-infected adults with microscopy- or culture-confirmed talaromycosis between October 2012 and December 2015 across Vietnam to receive amphotericin 0.7 mg/kg/day (N=219) or itraconazole 400 mg/kg/day (N=221) for two weeks, followed by itraconazole maintenance therapy in all patients. The primary outcome was mortality by two weeks. Secondary outcomes included mortality by week 24, time to clinical resolution, early fungicidal activity, disease relapse, immune reconstitution inflammatory syndrome (IRIS), and tolerability. Results Mortality by two weeks was 6.5% in the amphotericin group and 7.4% in the itraconazole group (absolute risk difference, 0.9 percentage points; 95% confidence interval [CI], -3.9 to 5.7 percentage points; non-inferiority P<0.0001); however, mortality risks by week 24 were 11.3% and 21.0%, respectively (absolute risk difference, 9.7 percentage points; 95% CI, 2.8 to 16.6 percentage points; P=0.006). Amphotericin was associated with significantly faster clinical resolution and fungal clearance, and lower rates of relapse and immune reconstitution inflammatory syndrome (IRIS). Patients on amphotericin experienced more infusion reactions, renal failure, hypokalemia, hypomagnesaemia, and anemia. Conclusions Amphotericin is superior to itraconazole as initial therapy for talaromycosis in terms of six-month mortality, clinical response, and fungicidal activity.